2014
DOI: 10.1007/s00330-014-3549-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved dopamine transporter binding activity after bone marrow mesenchymal stem cell transplantation in a rat model of Parkinson’s disease: small animal positron emission tomography study with F-18 FP-CIT

Abstract: • Mesenchymal stem cells were intravenously injected to treat the PD rats • Dopamine transporter binding activity was improved after stem cell therapy • Stem cell therapy induced functional recovery and preservation of dopaminergic neurons • The effect of stem cells was confirmed by FP-CIT PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In PD, BMSCs have the ability to regenerate damaged neurons [163,164]. Moreover, BMSCs can improve the dopamine transporter binding activity, which results in the recovery and protection of dopaminergic neurons [165]. Several clinical trials are conducted while using BMSCs on PD patients (NCT02611167, NCT01446614, NCT00976430).…”
Section: Bmscs Involved In the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…In PD, BMSCs have the ability to regenerate damaged neurons [163,164]. Moreover, BMSCs can improve the dopamine transporter binding activity, which results in the recovery and protection of dopaminergic neurons [165]. Several clinical trials are conducted while using BMSCs on PD patients (NCT02611167, NCT01446614, NCT00976430).…”
Section: Bmscs Involved In the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…MSCs have the ability to migrate to injury sites and promote repair, which makes them compelling candidates for systemic administration. Systemic administration of MSCs has been shown to be effective using BM-derived MSCs [124][125][126][127][128][129][130] and AD-derived MSCs 126 . In many of these studies, behavioral improvement, neuroprotective effects, and neurogeneration were observed.…”
Section: Route Of Delivery and Other Variabilitiesmentioning
confidence: 99%
“…The ideal material is visible under detecting instruments without the requirement for invasive methods [ 44 , 45 ]. Some researchers are exploring the utility of optogenetics, F-18 FP-CIT PET, and MION-Rh to measure the therapeutic effect of stem cells in PD [ 17 , 25 , 46 ]. These technologies can integrate the transplantation, cell viability, animal behavior, and histopathological evaluation to enable the identification of mechanisms that drive functional recovery.…”
Section: Discussionmentioning
confidence: 99%